Structure, morphology and annealing behavior of ion tracks in polycarbonate. (November 2018) - Schauries, D.; Mota-Santiago, P.; Gilbert, E.P.; Kirby, N.; Trautmann, C.; Kluth, P.
Graphical abstract: Highlights: Ion track formation in polycarbonate is characterized by a damage zone of ∼2.5 nm radius with a density deficit of ∼5% The stoichiometry of the damage track shows equal loss of C and O and increased H loss. Annealing leads to track recovery by diffusion predominately from a track halo area of ∼5 nm radius. Abstract: Ion tracks created in polycarbonate foils by irradiation with 2.2 GeV Au ions were characterized using a combination of small-angle x-ray and neutron scattering (SAXS/SANS) and Fourier transform infrared spectroscopy (FTIR). The ion tracks were found to consist of a cylindrical damage core with a radius of ∼2.5 ± 0.2 nm and a relative density approximately 5% below that of the pristine polycarbonate. Upon exposure to thermal annealing between 100 and 200 °C, the tracks were observed to double in size. Simultaneously, this led to a recovery in the density of the ion track, reaching a value just below that of the pristine polymer. A mechanism is proposed that explains this behavior by diffusion of radiolysis products/material flow into the under-dense track core from the surrounding region. Treatment of the tracks with UV radiation has shown no significant change in the track structure and size.